DEVELOPMENT OF FLIPBOOK TEACHING MATERIALS BASED ON CULTURE FUSION SEDATI TO IMPROVE CLASS V STUDENTS' SCIENCE LEARNING OUTCOMES SD NEGERI 45 BANDA ACEH - Ainal Mardhiah; Lili Kasmini; Siti Mayang Sari (International Journal of Cultural and Social Science, 2026)
This study aims to develop flipbook teaching materials based on Sedati culture fusion in the subject of science to improve the learning outcomes of fifth-grade students at SD Negeri 45 Banda Aceh. This research was conducted in Banda Aceh City as part of the study in the Master of Elementary Education Program at Bina Bangsa Getsempena University. The type of research used is Research and Development (R&D) with the ADDIE development model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The subjects of the study were fifth-grade students with the material "Harmony in Ecosystems". Data collection instruments included expert validation sheets (language, materials, and media), teacher and student response questionnaires to measure practicality, and learning outcome tests to measure effectiveness through N-Gain calculations. The results showed that the flipbook teaching materials based on Sedati culture fusion met the criteria of very valid based on expert assessments. From the practicality aspect, teacher and student responses showed a category of very practical and easy to use in learning. Meanwhile, the results of the effectiveness test showed an increase in student learning outcomes with a moderate to high increase category based on the N-Gain value. Thus, Sedati's culture fusion-based flipbook teaching materials are declared valid, practical, and effective in improving fifth-grade elementary school students' science learning outcomes and supporting the integration of local cultural values into contextual and meaningful learning.